Atomic layered deposition iron oxide on perovskite LaNiO3 as an efficient and robust bi-functional catalyst for lithium oxygen batteries. (10th August 2018) - Gong, Cheng; Zhao, Ling; Li, Shuai; Wang, Huanwen; Gong, Yansheng; Wang, Rui; He, Beibei
Abstract: The desirable physi-chemical properties of perovskite oxides make them the promising cathode materials of rechargeable Li-O2 batteries. Much attention is devoted to the structure design and the composite incorporation to develop the catalytic activity and durability of perovskite oxides used in the electrode. Herein, we propose an integration of atomic layered deposition iron oxide and perovskite LaNiO3 as a novel catalyst for both oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). Owing to the unique interconnected structure and the synergistic effect of Fe2 O3 and LaNiO3, the 6 nm thick Fe2 O3 /LaNiO3 hybrid catalyst demonstrates the considerable intrinsic activities, which favorably outperforms other the state of the art perovskite catalysts. In addition, the Li-O2 battery employing this tailored catalyst displays a significantly decreased reduced discharge/charge voltage gap of 0.77 V at 50 mA g −1 with good rate capability and considerable cycle stability, indicating the practical feasibility of Fe2 O3 /LaNiO3 hybrid as a promising oxygen electrode catalyst for Li-O2 batteries. This study highlights a new and feasible scheme to promote the bi-functionally of perovskite catalysts for the development of Li-O2 batteries and other electrochemical devises. Graphical abstract: Image 1 Highlights: An ultrathin ALD-Fe2 O3 /LaNiO3 hybrid catalyst is successfully prepared. ALD-Fe2 O3 /LaNiO3 exhibits enhanced bifunctional catalytic activity. Fe2 O3 /LaNiO3 based Li-O2 battery displays superior electrochemical performances.